Changes in drug use in European cities during early COVID-19 lockdowns – A snapshot from wastewater analysis. (August 2021) - Been, Frederic; Emke, Erik; Matias, João; Baz-Lomba, Jose Antonio; Boogaerts, Tim; Castiglioni, Sara; Campos-Mañas, Marina; Celma, Alberto; Covaci, Adrian; de Voogt, Pim; Hernández, Félix; Kasprzyk-Hordern, Barbara; et al.
Highlights: Wastewater analysis provided insights on drug use during the SARS-CoV-2 pandemic. Speculated decrease in consumption did not occur in all cities nor for all drugs. Measures had different effects, even at the regional level. Additional and complementary data needed to fully understand the impact on drug use. Abstract: The COVID-19 outbreak has forced countries to introduce severe restrictive measures to contain its spread. In particular, physical distancing and restriction of movement have had important consequences on human behaviour and potentially also on illicit drug use and supply. These changes can be associated with additional risks for users, in particular due to reduced access to prevention and harm reduction activities. Furthermore, there have been limitations in the amount of data about drug use which can be collected due to restrictions. To goal of this study was to obtain information about potential changes in illicit drug use impacted by COVID-19 restrictions. Wastewater samples were collected in seven cities in the Netherlands, Belgium, Spain and Italy at the beginning of lockdowns (March-May 2020). Using previously established and validated methods, levels of amphetamine (AMP), methamphetamine (METH), MDMA, benzoylecgonine (BE, the main metabolite of cocaine) and 11-nor-9-carboxy-Δ 9 -tetrahydrocannabinol (THC-COOH, main metabolite of tetrahydrocannabinol (THC)) were measured and compared with findings from previous years. Important differences in levels of consumed drugs were observed across the considered countries. Whilst for some substances and locations, marked decreases in consumption could be observed (e.g., 50% decrease in MDMA levels compared to previous years). In some cases, similar or even higher levels compared to previous years could be found. Changes in weekly patterns were also observed, however these were not clearly defined for all locations and/or substances. Findings confirm that the current situation is highly heterogeneous and that it remains very difficult to explain and/or predict the effect that the present pandemic has on illicit drug use and availability. However, given the current difficulty in obtaining data due to restrictions, wastewater analysis can provide relevant information about the situation at the local level, which would be hard to obtain otherwise.